Awareness, Attitude and Utilization of Orange-Fleshed Sweet Potato (OFSP): Critical Literature Review - Abujaja Afishata Mohammed (European Scientific Journal, ESJ, 2023)
The study relied on secondary data to review the level of awareness, attitude and utilization of Orange-Fleshed Sweet Potato (OFSP). The review was supposed to offer important information regarding how widely used and known OFSP was. Evidence from the study showed that although most countries were aware of OFSP's existence and its nutritional advantages, the market for OFSP was not yet formally established. Most of the studies also emphasized the statement that if OFSP is being processed into flour for making chips, biscuits, porridge, bread, drinks and other special forms of foods, consumers especially households would have accepted them to increase consumption. Socio-economic factors such as social class affects the level of utilization and preference patterns of the crop. Lack of storage facilities, lack of modern processing equipment and scarcity of OFSP vines had a great effect on its utilization. The study suggests that in order to increase agricultural value addition, OFSP farmers should be empowered through effective and efficient extension training on the usage of modern processing techniques.  Also, OFSP should be processed into several forms such as biscuit, breads, drinks and other special forms of foods for alternative income sourcing. Finally, study should be conducted on consumers’ willingness to pay for value added products made from OFSP.